1993
DOI: 10.1177/144078339302900205
|View full text |Cite
|
Sign up to set email alerts
|

Multiculturalists, Monoculturalists and the many in between: Attitudes to Cultural Diversity and their Correlates

Abstract: The most comprehensive survey of Australian attitudes to multiculturalism has been variously interpreted as showing that multiculturalism enjoys a high level of support or very little support at all. A re-analysis of the data suggests that both views are mistaken: while multiculturalists appear to outnumber monoculturalists, many Australians — perhaps most — are caught somewhere in between. Attitudes to multiculturalism correlate strongly with several things: views about assimilation, equal opportunity, govern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 1 publication
0
10
0
1
Order By: Relevance
“…Few studies have focused on the construct validity of multiculturalism (Berry, 2001;Breugelmans & Van de Vijver, 2004;Ginges & Cairns, 2000;Goot, 1993;Ho, 1990;Joppke, 1996;Nederveen Pieterse, 2001;Taylor & Lambert, 1996). Dutch studies (using different instruments for assessing attitudes toward multiculturalism) have shown that the concept of multiculturalism is unidimensional (Arends-Tóth & Van de Vijver, 2000;Breugelmans & Van de Vijver, 2004;Verkuyten & Thijs, 2002).…”
Section: Studies On the Concept Of Multiculturalismmentioning
confidence: 99%
“…Few studies have focused on the construct validity of multiculturalism (Berry, 2001;Breugelmans & Van de Vijver, 2004;Ginges & Cairns, 2000;Goot, 1993;Ho, 1990;Joppke, 1996;Nederveen Pieterse, 2001;Taylor & Lambert, 1996). Dutch studies (using different instruments for assessing attitudes toward multiculturalism) have shown that the concept of multiculturalism is unidimensional (Arends-Tóth & Van de Vijver, 2000;Breugelmans & Van de Vijver, 2004;Verkuyten & Thijs, 2002).…”
Section: Studies On the Concept Of Multiculturalismmentioning
confidence: 99%
“…Only a few studies have dealt with the psychological meaning of multiculturalism (Berry 2001; Breugelmans and van de Vijver 2004; Ginges and Cairns 2000;Goot 1993;Ho 1990;Joppke 1996;Nederveen Pieterse 2001;Schalk-Soekar and van de Vijver 2008;Taylor and Lambert 1996). Arends-To´th and van de Vijver (2003) administered an adapted version of the 10-item multicultural attitude scale by Berry and Kalin (1995) to more than 1,500 Dutch members of the majority group.…”
Section: Empirical Studies On Multiculturalismmentioning
confidence: 99%
“…On the whole, Australian multiculturalism has not been able to fully address institutionalized racism, particularly in relation to national identity (Castles and Vasta, 1996;Hage, 1998;Vasta, 1993). Two articles reviewing comprehensive data on attitudes towards multiculturalism (Goot, 1993) and Australian identity (Phillips, 1998) reveal a general ambivalence regarding the compatibility of cultural diversity with national values and ways of life. 'Celebrated by some and rejected by others, multiculturalism is controversial precisely because of its real and perceived (in)compatibility with national unity' (Stratton and Ang, 1998: 135).…”
Section: Discourses On Ethnicity and Multiculturalismmentioning
confidence: 99%